SBP Is Superior to MAP to Reflect Tissue Perfusion and Hemodynamic Abnormality Perioperatively - Sun, Jie; Yuan, Jing; Li, Bin (Frontiers in Physiology, 2021)
Many articles have reported that intraoperative low mean artery pressure (MAP) or low systolic blood pressure (SBP) impacts on organs’ function and patients’ outcomes perioperatively. On the contrary, what type of blood pressure should be obtained still needs to be clarified. In our paper, we compared the influencing factors of MAP and SBP, and mathematical formula, arterial pulse contour calculation, and cardiovascular physiological knowledge were adopted to discuss how blood pressure can effectively reflect tissue perfusion and hemodynamic abnormality perioperatively. We concluded that MAP can reflect cardiac output change sensitively and SBP can reflect stroke volume change sensitively. Moreover, SBP can reflect the early hemodynamic changes, organs’ perfusion, and heart systolic function. Compared with MAP, perioperative monitoring of SBP and timely detection and treatment of abnormal SBP are very important for the early detection of hemodynamic abnormalities.